Numerical simulation of thermo-mechanical behavior of floating energy pile-raft foundation - YANG Tao; CHEN Yang; KONG Gangqiang (Shenzhen Daxue xuebao. Ligong ban)
The 3D nonlinear finite element model is developed to investigate thermo-mechanical response of a piled raft equipped with floating energy piles on sand subjected to combined thermo-mechanical loadings. Attention is focused on thermally induced group effects， the variations in temperature of the surrounding soil and the effect of the number and the layout of the energy piles on the thermally induced additional axial stress in piles and the differential settlements among the pile heads. The results show that when all the piles are heated， the additional axial compressive stress is much smaller for a pile in the energy pile group than that for single energy pile in the same group. In a pile-raft foundation with partial energy pile， the additional axial compressive stress is distributed in parabolic shape along the energy pile， and it decreases with the increasing number of energy piles. While the additional axial stress in a non-energy pile is distributed in S shape， and the additional axial tensile stresses in the upper parts of non-energy corner piles and edge piles increase with the increase of the number of energy piles. The layout of energy piles has great influence on the additional axial stresses in the energy piles， but has insignificant effect on the additional axial stresses in the non-energy piles. The maximum differential settlement among the pile heads is larger when the layout of energy piles is asymmetrical. The temperature of the surrounding soil depends on the number of energy piles around it.